Constructing Students’ Identities through Social Media: A Case Study of Chinese Mainland Students in Macao - Jing, Jing (Journal of Modern Social Sciences, 2025)
The role of social media in young generation’s live become more salient nowadays, especially for them to searching for relationships and maintaining social connections. In the particular life transitions, social media provide adolescents amounts of resources to help them construct their new identities and cope with culture issues. In this study, I employ social comparison theory to explore how do Chinese mainland students in Macao use social media to manage their online and offline identities in different phases of college life. The research reveals that respondents experience affirmation, acculturation and integration from their past “Freshman” period to the present “Junior” period. Besides, social comparison plays a mainly negative role in handling students’ identities, which leads a series of difficulties and worries in their college life.